Thermodynamic analysis and optimization of a multi-stage compression system for CO2 injection unit: NSGA-II and gradient-based methods - Allahyarzadeh-Bidgoli, Ali; de Mello, Paulo Eduardo Batista; Dezan, Daniel Jonas; Saltara, Fábio; Salviano, Leandro Oliveira [UNESP]; Yanagihara, Jurandir Itizo (Springer Nature, 2021)
The injection of CO2 into oil reservoirs is used by the oil and gas industry for enhanced oil recovery (EOR) and/or the reduction of environmental impact. The compression systems used for this task work with CO2 in supercritical conditions, and the equipment used is energy intensive. The application of an optimization procedure designed to find the optimum operating conditions leads to reduced energy consumption, lower exergy destruction, and reduced CO2 emissions. First, this work presents two thermodynamic models to estimate the amount of power necessary for a multi-stage CO2 compression system in floating production storage and offloading (FPSO) using accurate polytropic relationships and equations of state. Second, a thermodynamic analysis using the first and second laws of thermodynamics is conducted to identify possible improvements in energy consumption and the sources of the compression unit’s irreversibilities. In the final step, optimization procedures, using two methods with different approaches, are implemented to minimize the total power consumption. As the number of stages and the pressure drop between them influence the total power required by the compressors, these are considered as the input parameters used to obtain the inlet pressure at each stage. Three different compositions with variations in CO2 content, i.e., pure CO2, pure CH 4, and 70% CO2 + 30% CH 4, are also investigated as three different operating scenarios. The optimal configurations and pressure ratios result in a reduction in power consumption of up to 9.65%, mitigation of CO2 emissions by up to 1.95 t/h, and savings in exergy loss of up to 23.9%, when compared with conventional operating conditions.
Keywords: CCUS; Energy consumption; Multi-stage compression; Optimization; Supercritical carbon dioxide